Performance Optimization and Characteristics of Different Refrigerants for Pump-driven Two-phase Cooling System - Wang Xuan; Ma Guoyuan; Zhou Feng (Zhileng xuebao)
A pump-driven two-phase cooling system was proposed for cooling and energy conservation at data centers. An experimental unit was built to study the effects of influencing factors like internal resistance of heat exchangers, face velocity of heat exchangers, mass flow rate, and type of refrigerant etc. on the performance of the unit. The results show that the decrease in internal resistance benefits the decrease in unit power and promotion of EER (energy efficiency ratio). Both too high and too low face velocity of heat exchangers is disadvantageous to the performance of the system. The performance of R32 is better than that of R22 under the working conditions of pump-driven two-phase cooling systems, but its feed liquid is insufficient under low frequencies of the pump when the outdoor temperature is high.